Navigating Digital Learning in the Infrastructure Gap: Adaptive PjBL Strategy in the RPL Department of Vocational High Schools - Nazli Nahrowi; Aura Adhy Cahyaningsih; Imroatus Sholihah; Maghfira Ulil Azizah; Zaenal Abdul Rahmandani (Universitas Negeri Surabaya, 2026)
Digital transformation in vocational education often encounters systemic barriers, particularly in resource-constrained settings where infrastructure gaps significantly contrast with industry demands. This study aims to analyze the navigation of Project-Based Learning (PjBL) strategies and technological adaptation in a Software Engineering (RPL) program facing extreme device scarcity. A qualitative descriptive case study was conducted at SMKN Takeran, Indonesia, involving one productive teacher and 36 students. Data were gathered through participatory observation, semi-structured interviews, and document analysis, subsequently processed using thematic analysis. The findings reveal that a device ratio of 1:12 does not halt digital transformation but instead triggers